The Relationship between the Application of Andragogical Principles and Package C Learning Motivation in PKBM Surya Amanah Pasaman District - Apmilia Wenty, Dyka; Sunarti, Vevi (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This research is motivated by the low learning motivation of residents studying package C for sociology subjects at PKBM Surya Amanah, Pasaman Regency, this is related to the application of the tutor's andragogy principle in learning activities. This type of research is correlational quantitative research. The population of this research is all residents studying package C PKBM Surya Amanah, totaling 96 people. While the samples taken were 50% of the population, namely 49 residents studied with stratified random sampling technique. Collecting data in this study using questionnaires and interviews to obtain initial data. With the data analysis technique using descriptive and correlational (product moment) and using the help of IBM SPSS (Statistical package and service solution) version 24. The results showed that: (1) the application of the principle of andragogy tutor package C in PKBM Surya Amanah was categorized quite low. (2) the motivation to learn package C at PKBM Surya Amanah is categorized as low. and (3) there is a significant relationship between the application of andragogy principles with learning motivation in package C at PKBM Surya Amanah, Pasaman Regency.Keywords: Application of Andragogy Principles, Learning Motivation